Go Jump in a Lake! - Jay M. Price (Symphony in the Flint Hills, 2018)
Introduction: A few years ago I was part of a group who gathered at Toronto Lake to explore the nature trails at Cross Timbers State Park. There was a birder whose attuned ears picked up on the faintest calls. There were plant experts who debated the genus and species of the stems and leaves we found on our walk.